(untitled) (Journal of Applied Learning and Teaching, 2022)
My principal concern in this paper is with matters associated with interpretive studies conducted as part of research projects deemed by their authors to be of a mixed-methods type. The stress throughout is on the importance when conducting an interpretive study as part of a research project where the plan is to also conduct a quantitative study, that researchers should, from the outset, make explicit how their selected research techniques can address their chosen topic. In other words, there is a need to indicate how one’s chosen area of research is connected, first to an underlying research paradigm, then to a specific theoretical position within the paradigm, then to a specific methodology consistent with the paradigm and the theoretical position, and finally to a set of methods for data gathering and analysis consistent with all of this.